Recent advancements and future insight of lead-free non-toxic perovskite solar cells for sustainable and clean energy production: A review. (October 2022) - Ikram, Muhammad; Malik, Rumesa; Raees, Rimsha; Imran, Muhammad; Wang, Feng; Ali, Salamat; Khan, Maaz; Khan, Qasim; Maqbool, Muhammad
Abstract: Production and management of clean energy in a sustainable manner is a global need. Several methods of energy production have been explored but some of them are accompanied with environmental hazards and toxic materials. One of those several means of sustainable energy production is a perovskite solar cell. Perovskite solar cells have received interest for photovoltaic applications attributed to their verified over 25% power conversion efficiency. Because of the high toxicity associated with lead, it seems a pressing need to clean and remove toxic lead from currently available and future inorganic Perovskite solar cells. Environmental-health hazards are posed by lead-based compounds and devices available for use. This review focuses on the development of lead-free non-toxic perovskite materials based solar cells and other devices. To solve the lead associated toxicity problem, lead can be substituted with nontoxic and environmentally friendly metals like Ti, Sn, Sb, Ge, Bi, and Ag. To further enhance the stability of lead-free perovskites, all-inorganic lead-free perovskites have recently gotten considerable attention. In numerical simulation, the CsSnI3 based perovskite solar cell has the highest power conversion efficiency of 28.97% among all the lead-free perovskite based devices. Extensive review of environmentally friendly and toxicity free perovskites and their applications has been performed. The advantages of lead substituted metals have been discussed. Lastly, critical analysis and discusses is reported on the progress to enhance the efficiency and stability of lead-free perovskite solar cells and devices by energy-band engineering and inorganic transport layers.